Physiological and anatomical comparison between four different apple cultivars under cold-storage conditions - Ghafir, Saleh A. M. (Acta Biologica Szegediensis, 2009)
The work was carried out in two successive seasons to investigate the storability of four apple cultivars viz. Golden Delicious, Starking Delicious, Star Cremson and Gala, which were grown under El Jabal El Akhdaer conditions, in Libya. Fruits were harvested and stored at 85-90% relative humidity and 0ºC for 0, 30, 60, 90, 120, 150 and 180 days. The obtained results exhibited the significant differences between the tested cultivars in the studied parameters comprising physiological and anatomical parameters. The fruits of Star Cremson cv. had a potentially good storage properties, as they showed less weight loss, while those of Gala cv. had the highest level of weight loss. On the other hand, Golden Delicious cv. gave the highest values of fruit firmness, while the lowest values were obtained in fruits of Starking Delicious and Star Cremson cvs. fruits. Fruit weight loss % increased, while other studied parameters (firmness rate, TSS%, starch concentration and acidity%) decreased gradually by extending storage period. Anatomical data demonstrated that fruit surface of cvs. Gala and Star Cremson were smooth, while undulate and ripples surfaces were obtained in Starking Delicious and Golden Delicious cvs., respectively at the end of cold storage. Gala fruits had the thick cuticle layer compared to the other cultivars. Crushed parenchymatous cells (cpc) were found in storage tissue in Starking Delicious and Golden Delicious. It may be concluded that the results indicated a great variability among cultivars. All studied parameters of four apple cultivars reduced during cold-storage periods. The highest fruit storability was achieved for Star Cremson.